Shifting Marriage Customs in the Clans of the Kenegerian Air Tiris Community, Kampar Regency - Misrulina Misrulina; Ahmal Ahmal; Yuliantoro Yuliantoro (CV. Rayyan Dwi Bharata, 2024)
The purpose of this research is to find out the reasons for the ban on marriage between ethnic groups in the Air Tiris community, to find out the reasons for the shift in ethnic marriage traditions in the Air Tiris community, and to determine the impact of the shift in ethnic marriage traditions in the Air Tiris community. This research uses qualitative research methods, with data collection techniques in the form of observation, interviews and documentation. The subjects in this research were 1 tribal chief from the Air Tiris state, 1 person who committed marriages between tribes, 1 community member from the Air Tiris state, 3 young men and women from the Air Tiris state. The results of this research indicate a shift in tribal marriage traditions in the Air Tiris community, Kampar district. The causes of the shift in traditions in the people of the Water Water Country are educational factors, religious factors, economic factors and globalization factors. The impact of the shift in traditions in the people of Air Tiris is that people are starting to ignore the traditions that have been in effect for generations in society.